Nonwoven Ion-Exchange Membranes with High Protein Binding Capacity for Bioseparations - Solomon Mengistu Lemma; Cristiana Boi; Ruben G. Carbonell (Membranes, 2021)
This study presents the preparation and characterization of UV-grafted polybutylene terepthalate (PBT) ion exchange nonwoven membranes for chromatographic purification of biomolecules. The PBT nonwoven was functionalized with sulfonate and secondary amine for cation and anion exchange (CEX and AEX), respectively. The anion exchange membrane showed an equilibrium static binding capacity of 1300 mg BSA/g of membrane, while the cationic membranes achieved a maximum equilibrium binding capacity of over 700 mg hIgG/g of membrane. The CEX and AEX membranes resulted in dynamic binding capacities under flow conditions, with a residence time of 0.1 min, of 200 mg hIgG/mL of membrane and 55 mg BSA/mL of membrane, respectively. The selectivity of the PBT-CEX membranes was demonstrated by purifying antibodies and antibody fragments (hIgG and scFv) from CHO cell culture supernatants in a bind-an-elute mode. The purity of the eluted samples exceeded 97%, with good log removal values (LRV) for both host cell proteins (HCPs) and DNA. The PBT-AEX nonwoven membranes exhibited a DNA LRV of 2.6 from hIgG solutions in a flow-through mode with little loss of product. These results indicate that these membranes have significant potential for use in downstream purification of biologics.